Is the Medium the Message? A Consideration of Whether the Internet Can be Used Effectively for Astrological Consultations. (22nd February 2019) - Clynes, Frances
Abstract : While a large body of literature exists on the practice and validity of online religious activity and rituals, to date no literature exists investigating the validity of the online astrological consultation and whether or not the medium of the Internet can inﬂuence the connection between astrologer and client. My initial qualitative research with sixty-ﬁve astrologers, conducted between 2012 and 2014, revealed that over sixty percent of astrologers use the Internet for astrological consultations with clients. Taking this number as my dataset, my aim was then to investigate whether, when astrologers conducted consultations for clients online, the chart continued to have agency in creating a meaningful consultation space. My results showed that the online medium did not impact on the message or content of the consultation and that, as in face-to-face astrological consultations, the effectiveness and validity of the consultation was independent of the media used to hold it.